THE INTERFERENCE OF RECIPROCAL TEACHING METHOD IN READING COMPREHENSION SKILLS AT GRADE XI OF NUSATAMA VOCATIONAL HIGH SCHOOL PADANG - Dwi Megista Putri (Menara Ilmu, 2018)
This research investigated interference of using reciprocal method in improving students’reading comprehension at grade XI of vocational high school. A total of 42 studentsidentified with diagnostic reading participated. The sample was divided into two groups;experimental(n= 21 girls)and control (n=21girls). T-test was employed for data analysis.Findings from this study indicated the effectiveness of reciprocal method interference inimproving reading comprehension in the target students. On the basis of the findings,the study aimed for theeffectiveness of reciprocal method inimproving students’ readingcomprehension.Keywords : Interference of reciprocal method, reading comprehension.